THE INFLUENCE OF OBSTRUCTIVE SLEEP APNEA AND PRIMARY SNORING ON CARDIAC ARRHYTHMIAS AND HEART RHYTHM VARIABILITY IN PATIENTS WITH ISCHEMIC HEART DISEASE - E. S. Tarasik; A. G. Bulgak; N. V. Zatoloka (Евразийский Кардиологический Журнал, 2016)
The aim. The study and analysis of cardiac arrhythmias, heart rhythm variability in patients with ischemic heart disease, obstructive sleep apnea and primary snoring. Material and methods. 65 patients aged 40-68 with ischemic heart disease, obstructive sleep apnea and primary snoring have been included in research. Results. Obstructive sleep apnea and primary snoring leads to an increase in sympathetic and parasympathetic activity of autonomic nervous system on sinus node in patients with ischemic heart disease, obstructive sleep apnea and primary snoring.